Cilvēku motivācija ilgstoši strādāt vienā uzņēmumā - Zamkovaja, Marija (Latvijas Universitāte, 2008)
Cilvēku motivācija ilgstoši stradāt vienā uzņēmumā. Bakalaura darbs. Rīga 2008. Darba apjoms sastada 70 lpp. Darbs ir papildināts ar intervijas jautājumiem, kurus izmantoju ekspertintervijām, ar anketas jautājumu, kuru izmantoju darbinieku nozīmīgāka motīva noteikšanai, kā arī ar vienas intervijas transkriptu. Darba izstrādes procesā tika izmantoti teorētiskie avoti, internēta avoti, kā arī tika veikta dokumentu analīze, un tika veiktas padziļinātas intervijas un novērošanas metode. Pētījuma ietvaros tika pētīti 2 Latvijas uzņēmumi: SIA Dardedzes Hologrāfija un SIA Fan. Šī darba galvenie uzdevumi ir noskaidrot darbinieku motivāciju ilgstoši strādāt vienā uzņēmumā. Darbs sastav no teoretiskas un empiriskas daļas.

The subject of this bachelor paper is Motivation of employees to work at the same place for a lengthy period of time. This paper consists of 70 pages. The paper has several appendixes; such as questions of the interview, which I have used for interviewing experts, questionnaire, which was used to find out the opinion of the employees on the motivation issues in their companies and results of which I have analyzed in my paper, and also a transcript of one of the interviews. In the process of writing the paper the author has used theoretical sources, internet supplies. Also the author has analyzed various documents and papers and has conducted thorough and detailed interviews as well as used the observation method. This paper is based on the research done in 2 Latvian enterprises – Dardedze holografija Ltd and Fan Ltd. The main mission of this paper is to find out what is the motivation for the employees to work in one and the same company for a lengthy period of time. This paper consists of theoretical and empirical parts.
Human Motivation for Long-term Employment in Same Company
Keywords: Socioloģija